Taguchi-based grey relational study for multiple criterion optimization on process variables for micro Electro-chemical Machining of Inconel Super-alloy. (2022) - Selvan, T.A.; Sivaram Kotha, M.N.V.S.A.; Swamy Chinamilli, N.V.S.; Guru Dattatreya, G.S.; Rajesh, S.; Akshey, P.B.; Madhankumar, S.
Abstract: The findings of Inconel 718 super-alloy on material extracting potential, including surface finish, were examined in this research. The investigation was conducted out using micro electrochemical metalworking with different factors and a titanium rod material as a tool. Utilizing Minitab 19 software, the optimizing approach has been predicated on Taguchi's related gray relational procedure. The Taguchi's approach was used to create significant attributes for the L9 orthogonal string, utilizing three input factors: voltage (VT), electrolyte concentration (EC), and current (CT). Taguchi's design assessment was used to evaluate the influence of input factors on the process of dissolving and machined surface quality of the material. Regression techniques were established for forecasting. Finally, the best test array for material removal rate was 16 V, 0.40 mol/lit, and 0.8 amp. The superior surface roughness test array was 9 V, 0.41 mol/lit, and 1 amps. According to the grey relational analysis, array number three produced the best results.